2022
DOI: 10.47487/apcyccv.v3i4.236
|View full text |Cite
|
Sign up to set email alerts
|

Acute and long-term success of ventricular tachycardia ablation in patients with ischemic heart disease in a Mexican center

Abstract: Objective. To report the results of ventricular tachycardia (VT) catheter ablation in ischemic heart disease (IHD), and to identify risk factors associated with recurrence in a Mexican center. Materials and methods. We made a retrospective review of the cases of VT ablation performed in our center from 2015 to 2022. We analyzed the characteristics of the patients and those of the procedures separately and we determined factors associated with recurrence. Results. Fifty procedures were performed in 38 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The authors identified ICD shocks, basal anteroseptal VT origin, and procedural failure as predictors of VT recurrence [12]. In contrast to the previous study, a recent, smaller analysis of 50 cases included a majority of ischemic heart disease patients [13]. This study revealed that along with atrial fibrillation and advance heart failure, female sex appears to pose a higher risk of post-ablation VT recurrence.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The authors identified ICD shocks, basal anteroseptal VT origin, and procedural failure as predictors of VT recurrence [12]. In contrast to the previous study, a recent, smaller analysis of 50 cases included a majority of ischemic heart disease patients [13]. This study revealed that along with atrial fibrillation and advance heart failure, female sex appears to pose a higher risk of post-ablation VT recurrence.…”
Section: Discussionmentioning
confidence: 92%
“…Multiple factors have been identified that contribute to the success of the procedure including lower LVEF, multiple inducible VT morphologies, impaired NYHA functional status, presentation with an electrical storm, and non-ischemic VT [11][12][13][14]. Despite the extensive literature on the predictors of VT recurrence, there is a paucity of machinelearning-based analyses.…”
Section: Introductionmentioning
confidence: 99%